2003
DOI: 10.1002/ijc.11585
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of death receptor and mitochondrial apoptosis signaling in resistant human NSCLC in vivo

Abstract: Non small cell lung carcinoma (NSCLC) is a highly lethal malignancy that often becomes resistant to chemotherapy. To determine whether alterations in apoptotic signaling might contribute to such resistance, we established in vitro and in vivo models for sensitive and resistant human NSCLC. We found that resistance is due to multiple defects found in expression of CD95-L, CD95 and members of the Bcl-2 and IAP family, as well as caspase-8, -9 and -3 as examined by immunohistochemistry, Western blot analysis, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…These data indicate that Numb may be involved in conferring cisplatin sensitivity to MPM cells. Decreased caspase-3 and caspase-9 activation have been described as an additional mechanism of cisplatin resistance in various types of cancers (41)(42)(43)(44). To confirm whether or not Numb sensitizes MPM cells to cisplatin through the caspasedependent apoptotic pathway, further investigation is needed.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that Numb may be involved in conferring cisplatin sensitivity to MPM cells. Decreased caspase-3 and caspase-9 activation have been described as an additional mechanism of cisplatin resistance in various types of cancers (41)(42)(43)(44). To confirm whether or not Numb sensitizes MPM cells to cisplatin through the caspasedependent apoptotic pathway, further investigation is needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple results suggest that the classical caspase-dependent apoptotic pathways are not functional in NSCLC cells in response to cytotoxic agents in vitro (Yang et al, 2003;Bartling et al, 2004;Broker et al, 2004) and this may also be the case in vivo (Ferreira et al, 2001a, b). As an example, chemoresistant NSCLC exhibit a reduced expression of caspase-9 or caspase-3 (Okouoyo et al, 2004). We previously identified the U1810 cells as the most radioresistant among a panel of NSCLC cell lines (Joseph et al, 2001).…”
Section: Menadione Enhances the Susceptibility Of U1810 Cells To Apopmentioning
confidence: 99%
“…One therapeutic option that has been proposed to overcome resistance is the restoration of the defective caspase-dependent cell death pathway (Fennell, 2005). Overexpression of caspases in drug-resistant human NSCLC xenografts may overcome chemoresistance in vivo (Okouoyo et al, 2004). Pharmacological inhibition of IAP proteins restored NSCLC cells apoptosis sensitivity in vitro and in vivo, in mice grafted with human NSCLC (Yang et al, 2003).…”
Section: Menadione Enhances the Susceptibility Of U1810 Cells To Apopmentioning
confidence: 99%
“…12 It has been reported that the mechanisms of cisplatin resistance involve increased repair or tolerance of DNA damage and changes, such as failed caspase-9 activation, in apoptotic signaling pathways. 13,14 Hence, novel strategies to monitor disease progression and to improve responses to cisplatin therapy are required.…”
Section: Introductionmentioning
confidence: 99%